2011
DOI: 10.4319/lo.2011.56.6.2233
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal stability of a flexible algal–cnidarian symbiosis in a highly variable temperate environment

Abstract: We evaluated the seasonal stability of two algal symbiont populations in the temperate intertidal sea anemone Anthopleura elegantissima on San Juan Island, Washington, where the relatively thermally tolerant dinoflagellate Symbiodinium muscatinei coexists with the less thermally tolerant chlorophyte Elliptochloris marina. Random collection of anemones along repeatedly sampled transects over four seasons and three shore heights revealed S. muscatinei to be the dominant symbiont, with E. marina mostly limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 34 publications
(80 reference statements)
2
32
0
Order By: Relevance
“…Another consideration is that E. marina chlorophyll content does not always change predictably in response to changes in irradiance. Elliptochloris marina living within A. elegantissima show little seasonal variation in cell-specific chlorophyll content despite large fluctuations in irradiance (Verde and McCloskey, 2007;Dimond et al, 2011). We have also found that E. marina chlorophyll content within A. elegantissima does not consistently increase during long-term experimental shading (J.L.D., B.L.B.…”
Section: Photosynthetic Efficiency After Acclimation To Low-lightmentioning
confidence: 51%
See 2 more Smart Citations
“…Another consideration is that E. marina chlorophyll content does not always change predictably in response to changes in irradiance. Elliptochloris marina living within A. elegantissima show little seasonal variation in cell-specific chlorophyll content despite large fluctuations in irradiance (Verde and McCloskey, 2007;Dimond et al, 2011). We have also found that E. marina chlorophyll content within A. elegantissima does not consistently increase during long-term experimental shading (J.L.D., B.L.B.…”
Section: Photosynthetic Efficiency After Acclimation To Low-lightmentioning
confidence: 51%
“…and chlorophyte (Elliptochloris marina) symbionts. Relative to Symbiodinium muscatinei, E. marina exhibits low tolerance of high light and temperature, and is typically found in cooler, low-light habitats (Bates, 2000;Verde and McCloskey, 2001;Verde and McCloskey, 2002;Secord and Muller-Parker, 2005;Dimond et al, 2011). Interestingly, however, E. marina occurs approximately 6degrees of latitude farther south and much higher in the intertidal zone in A. xanthogrammica than in A. elegantissima (Secord and Augustine, 2000), indicating that host factors have an important effect on symbiont distribution patterns.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This bears some similarity to Hydra viridis (green hydra), which produces female gonads only if the Chlorella algal symbiont is present [40]. Although E. marina is less tolerant of high temperature and irradiance [17][18][19] and consistently less productive than S. muscatinei on a per-cell basis [41], the growth rate of E. marina is higher [19,21], and in habitats where irradiance and temperature are low year round, A. elegantissima commonly hosts E. marina at up to twice the density of S. muscatinei [20,28]. Thus, zoochlorellate A. elegantissima may be nearly as productive as zooxanthellate individuals under some conditions [19,28], but appear to direct more energy to sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Locally, A. elegantissima begin developing gonads in January, spawn from August to October [27] and are exposed to the harshest physical stresses during mid-day summer low tides [28]. Shields were used to reduce natural irradiance in each of three treatment groups, approximating conditions that favour zooxanthellate, zoochlorellate and aposymbiotic anemones, respectively [20]: ultraviolet (UV)-transparent acrylic shield for 85% irradiance, UV-transparent acrylic shield plus a layer of window screen for 43% irradiance and opaque grey PVC shield for 2% irradiance.…”
Section: Materials and Methods (A) Anemone Experimentsmentioning
confidence: 99%